Dual-functional polyethersulfone composite nanofibrous membranes with synergistic adsorption and photocatalytic degradation for organic dyes. (20th October 2020) - Xu, Yuanting; Lin, Wanting; Wang, Hui; Guo, Jiabei; Yuan, Dandan; Bao, Jianxu; Sun, Shudong; Zhao, Weifeng; Zhao, Changsheng
Abstract: How to remove environmental contaminants from wastewater has attracted widespread attentions in recent years. Herein, dual-functional polyethersulfone (PES) composite nanofibrous membranes with synergistic adsorption and photocatalytic degradation profiles for organic dyes were prepared through the combination of blending modification and electrospinning technology. Poly (acrylic acid-co-methyl methacrylate) copolymer was synthesized firstly; then the copolymer and PES were dissolved in a uniform TiO2 suspension, and followed by an electrospinning process to fabricate composite nanofibrous membranes. The obtained membranes could adsorb rhodamine B (RhB) dye in dark via electrostatic attraction, and the residual RhB dye was further degraded under UV irradiation. More importantly, the synergistic effects of adsorption and photodegradation were explored. On one hand, the adsorption accelerated the photodegradation process owing to the easy access for catalyst-contaminants contacting. On the other hand, the photodegradation eliminated the residual toxins more completely, and realized the regeneration of adsorption active sites by continuous UV irradiation but without any other treatments. The excellent recyclability of 95% removal ratio even after 5 cycles was obtained via this green way. Additionally, the composite membranes could also adsorb and photodegrade various other dyes and applied in the treatment for mixed dye solutions. Thereby, this synergistic adsorption and photocatalytic degradation will provide useful insights to design highly efficient and green materials for environmental wastewater remediation. Graphical abstract: Image 1